Regulation of lymphoma in vitro by CLP36 through the PI3K/AKT/CREB signaling pathway - Chao Lv; Guannan Chen; Shuang Lv (PeerJ, 2024)
Background CLP36 is also known as PDZ and LIM Domain 1 (PDLIM1) that is a ubiquitously-expressed α-actinin-binding cytoskeletal protein involved in carcinogenesis, and our current study aims to explore its involvement in lymphoma. Methods Accordingly, the CLP36 expression pattern in lymphoma and its association with the overall survival was predicted. Then, qPCR was applied to gauge CLP36 expression in lymphoma cells and determine the knockdown efficiency. The survival, proliferation and apoptosis of CLP36-silencing lymphoma cells were tested. Cell viability, proliferation and apoptosis were assessed based on cell counting kit-8 (CCK-8) assay, colony formation assay, EdU staining, and flow cytometry, respectively. Additionally, qPCR was used to calculate the expressions of proteins associated with metastasis and apoptosis, while immunoblotting was employed to determine the phosphorylation status of phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/cAMP-response element binding protein (CREB). Results CLP36 expression was relatively higher in lymphoma, which was associated with a poor prognosis. Also, CLP36 was highly-expressed in lymphoma cells and the silencing of CLP36 contributed to the suppressed survival and proliferation as well as the enhanced apoptosis of lymphoma cells. Further, CLP36 silencing repressed the expressions of Cadherin 2 (CDH2) and Vimentin (VIM) yet promoted those of Bax and Caspase 3 in lymphoma cells, concurrent with the reduction on the phosphorylation of PI3K, AKT and CREB, all of which were confirmed to be positively correlated with CLP36. Conclusion This study, so far as we are concerned, provided evidence on the involvement of CLP36/PI3K/AKT/CREB axis in lymphoma, which may be contributive for the identification on the relevant molecular targets of lymphoma.